MUHAMMADIYAH LEARNING METHODS AND THEIR IMPACT ON GRADE VII STUDENTS AT SMP MUHAMMADIYAH 5 SURAKARTA - Azzahra, Kayla; Shobahiya, Mahasri (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The learning method is a circle that connects teachers, students and learning materials. Teachers can use methods to deliver learning materials to students. This study aims to analyze the effectiveness of the lecture method in Muhammadiyah learning and its impact on grade VII students at SMP Muhammadiyah 5 Surakarta. The research method used is descriptive qualitative with a phenomenological approach, where data is collected through observation, interviews, and document studies. The results of the study indicate that the lecture method has advantages in delivering material systematically and effectively in reaching all students at one time. However, this method also has weaknesses, such as low student participation, boredom in learning, and lack of in-depth exploration and interaction. The positive impacts found include increased student understanding of the history and principles of Muhammadiyah, while negative impacts include student boredom and minimal motivation to learn independently. Based on these findings, it is recommended to combine the lecture method with other learning methods, such as discussion, use of interactive media, and giving project-based assignments to improve the effectiveness of Muhammadiyah learning in Muhammadiyah schools.